MAINTENANCE ALAT TENSI METER DIGITAL & ANALOG, STETOSKOP, TIMBANGAN DIGITAL & ANALOG OLEH MAHASISWA ELEKTROMEDIS DI SEMARANG BARAT - Nanda Aulya Septhiara; Aqila Nafis Mafaza, Cahaya Sayyidina (JOURNAL OF COMMUNITY DEDICATION, 2024)
Many nurses, doctors and even people around our environment use health equipment such as blood pressure meters, stethoscopes and digital scales to check our health with these devices. These tools are easy to find and the price is even cheap enough for everyone to be able to buy them, so many tools are thrown away if they can no longer be used again, even though the damage is trivial, but people prefer to replace them with new items. This community service focuses on maintaining medical equipment through developing students' soft skills in an effort to reduce the level of damage to medical equipment in the West Semarang environment. The aim of this activity is the association's work program by providing students with skills that can repair medical devices.